(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The marketing industry is vibrant and dynamic; trends, technologies, and strategies are always evolving. That’s why it’s vital that your company keeps up with new developments in the field. Monitoring marketing data is a smart approach to staying current with emerging market trends. Statistics reveal demographic details about a region’s potential customers, including their numbers, ages, incomes, and preferences. Data may be employed to identify key rivals, their customer base, and patterns in the lifespan of their products as part of competition analysis. Digital marketing represents a more versatile kind of advertising than old approaches and has seen a number of advancements and improvements. This leads to quicker positive effects than previous techniques. Promoting things online is less expensive than doing so through a physical store. By creating a profile of consumers’ buying habits and preferences, internet marketing enables the personalization of proposals to customers. Social networks spread widely very quickly. It is the most effective website available, allowing a company to easily reach numerous individuals. In spite of its benefits and drawbacks, digital marketing has a bright future for the lengthy viability of the item or service in the evolving technology market.